IMPACT OF THE DOUBLING FARMERS’ INCOME (DFI) PROGRAMME ONKNOWLEDGE, ADOPTION, PRODUCTIVITY AND INCOME OF GROUNDNUTGROWERS IN NAGARKURNOOL DISTRICT OF TELANGANA - B. RAJASHEKAR, M. JAGAN MOHAN REDDY, T. PRABHAKAR REDDY, O. SHAILA; M. RAJASHEKHAR (The Journal of Research, PJTSAU, 2026)
Groundnut is one of the major oilseed crops of southern Telangana and contributes substantially to the livelihood of small and marginal farmers, with Nagarkurnool district alone accounting for just over half of the State entire groundnut growing area. Despite the availability of improved production technologies, adoption has remained suboptimal because of limited technical knowledge, inadequate extension support and resource constraints. To address these gaps, Krishi Vigyan Kendra (KVK), Palem implemented the Doubling Farmers’ Income (DFI) Programme, promoting scientific groundnut production technologies through demonstrations, farmer training, exposure visits and regular technical advisories. The present study assessed the programme’s impact on knowledge, adoption, productivity and income of beneficiary farmers. An ex-post facto research design was employed with 240 beneficiary farmers selected from Nandivaddeman village (Bijinapally Mandal) and Gummakonda village (Thimmajipet Mandal), 120 respondents from each. Overall mean knowledge and adoption of nineteen recommended best management practices rose from 35.11% and 32.10% before the programme to 89.26% and 84.25% after it. Pod yield increased by 26.6% (2,180 to 2,760 kg ha-1), net income by 51.3% (Rs. 74,200 to Rs. 1,12,300 ha-1) and the Benefit–Cost ratio from 1.46 to 2.01; paired t-tests confirmed that gains in knowledge, adoption, yield and income were all highly significant (p < 0.01), with Cohen’s d exceeding 1.0 throughout, indicating large effect sizes. Chi-square tests of association further confirmed that the before-after increase in adoption was statistically significant for every one of the nineteen practices individually (p < 0.001), with Cohen’s h consistently above 1.0, the largest effects recorded for practices seed treatment, soil testing, Integrated Pest Management that had the lowest pre-programme adoption base. The study demonstrates that integrated demonstration-led extension interventions under DFI significantly improved groundnut productivity and profitability among resource-poor farm households in Nagarkurnool district. Beneficiaries showed predominantly medium risk orientation but high innovativeness and achievement motivation, a behavioural profile consistent with the breadth of adoption observed; the high cost of fertilizers and plant-protection chemicals, labour scarcity, erratic rainfall, disease incidence and delayed seed availability were the constraints most frequently cited by farmers, closely mirrored by their own suggestions for subsidized inputs, stronger price support, continued training and expanded custom-hiring access.